Giant Fibroma in Mayer-Rokitansky-Kuster-Hauser (MRKH) Syndrome Patient: A Case Report - Dao, Le Thi Anh; Huynh, Do Khac; Tri, Nguyen Manh (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2018)
MRKH syndrome is a rare form of genital malformation (the incidence is for 1/4000-5000 people). The MRKH patient shows no sign of uterus although its two annexes develop normally. People with MRKH do not have periods although their secondary sexual signs are normal. The fact that the fibrous cells in the Müller's fibrous strand grow into uterine fibroid tumors is very rare but often causes difficulties in diagnosing the origin of the tumor. Surgical removal of the tumor to prevent other tumors from developing is the most effective treatment.  Keywords Mayer-Rokitansky-Kuster-Hauser, fibroma. References [1] T M Chandler, L S Machan, , P L Cooperberg, et al. (2009). Mullerian duct anomalies: from diagnosis to intervention. Br J Radiol. 82(984): 1034–1042.doi: 10.1259/bjr/99354802. [2] He J1, Xu J, Zhou HY. (2016). Uterus- like mass: A very rare and elusive entity a case report. Medecine. Vol 95 Issiue 39- p e4961. doi: 10.1097/MD.0000000000004961. [3] Rawat KS1, Buxi T, Yadav A, et al (2013). Large leiomyoma in a woman with Mayer- Rokitansky- Kuster_ Hauser syndrome.J Radiol Case Rep. Mar 1;7(3):39-46. doi: 10.3941/jrcr.v7i3.1267. Print 2013 Mar. Large leiomyoma in a woman with Mayer-Rokitansky-Kuster-Hauser syndrome. [4] Sharma R.,1,*, Guleria K.1, Suneja A.1 et al (2017). Giant leiomyoma with extensive myxoid degeneration in Mayer- Rokitansky- Kuster_ Hauser syndrome. International Federation of Gynecology and Obstetrics. volume 138(1):125-127. DOI: 10.1002/ijgo.12162. [5] Barbara L. Hoffman,John O. Schorge,Karen D. Bradshaw. (2016) Chapter 9 Pelvic mass.William Gynecology 23 (2016) 202-230. Publishing Mc Graw Hill Education.